Desempleo y reforma laboral en España durante la Gran Recesión - Elíes Furió Blasco; Matilde Alonso Pérez (Cahiers de Civilisation Espagnole Contemporaine)
The chronic problems of the Spanish labor market have dramatically reappeared during the current Great Recession. Besides being astonishingly high, the Spanish unemployment rate is extremely volatile compared to other countries. This paper analyzes the main changes of the new labor market reform approved in Spain in 2012 in relation to the labor market situation. The reform aims to achieve higher internal flexibility to get an adjustment to business cycle fluctuations. However, it fails in other relevant areas, like suppressing dualism, improving the effectiveness of active labor market policies, enhancing productivity and maintaining the level of social protection of workers.